Answer:The final solution is all the values that make
x ( x − 16 ) = 0
true.
Step-by-step explanation:
Factor x out of
x ^2 − 16 x .
Factor x out of x
2 . x ⋅ x − 16 x = 0
Factor x out of
− 16 x . x ⋅ x + x ⋅ − 16 = 0
Factor x out of x ⋅ x + x ⋅ − 16
. x ( x − 16 ) = 0
If any individual factor on the left side of the equation is equal to
0 , the entire expression will be equal to 0
x = 0 x − 16 = 0
Set the first factor equal to 0
. x = 0
Set the next factor equal to 0
and solve.
Set the next factor equal to 0
x − 16 = 0
Add 16 to both sides of the equation.
x = 16
The final solution is all the values that make
x ( x − 16 ) = 0
true.
x = 0
, 16